Investigations on Wear Behavior of Aluminium Composites at Elevated Temperature. (27th June 2022) - Senthil Kumar, B. R.; Gopalarama Subramaniyan, G.; Pragadish, N.; Venkatesh, P. M.; Sanjay, Soni; Velu, C. M.; Navaneethakrishnan, G.; Vellingiri, Suresh; Govindarajan, Venkatesan
Abstract : The aerospace aluminium alloy AA7050 was reinforced with Al2 O3 of average particle size 5 m in this study using the stir casting method. To eliminate surface imperfections, AA7050/Al2 O3 composites with varied weight percentages (0, 2, 4, 6) were manufactured, and wear tests on composites were carried out utilizing a pin-on-disc apparatus that varied load, velocity, temperature, and weight %. The tensile and hardness tests were carried out at a high temperature. The inclusion of particles enhances wear resistance by establishing a mechanically mixed layer (MML), according to the findings. The wear resistance at 300°C was 100% higher in comparison with resistance at 150°C. Because of the Orowan strengthening and Hall–Petch effect, the tensile strength and hardness of composites enhanced. Temperature, tracked by the weight % of strengthening powders, was the most important factor that influences the wear resistance of the composites. The findings showed that the material properties of AA7050/4wt%Al2 O3 at 150°C and AA7050/2wt%Al2 O3 at 300°C are superior than base alloy.